Cicada fossils (Cicadoidea: Tettigarctidae and Cicadidae) with a review of the named fossilised Cicadidae - Moulds, M. S. (Zootaxa, 2018)
The Cicadoidea comprise two families, the Cicadidae and the Tettigarctidae. This paper evaluates the status and taxonomy of all named Cicadoidea fossils belonging to the Cicadidae. Shcherbakov (2009) has previously revised the Tettigarctidae. Two new genera are described, Camuracicada gen. n. and Paleopsalta gen. n., for Camuracicada aichhorni (Heer, 1853) comb. n. and Paleopsalta ungeri (Heer, 1853) comb. n. A lectotype is designated for Cicada emathion Heer, 1853.          Cicada grandiosa Scudder, 1892 is transferred to Hadoa Moulds, 2015 as Hadoa grandiosa comb. n.; Oncotympana lapidescens J. Zhang, 1989 is transferred to Hyalessa China, 1925 as Hyalessa lapidescens comb. n.; Meimuna incasa J. Zhang, Sun & X. Zhang, 1994 and Meimuna miocenica J. Zhang & X. Zhang, 1990 are transferred to Cryptotympana Stål, 1861 as Cryptotympana incasa comb. n. and Cryptotympana miocenica comb. n.; Tibicen sp. aff. japonicus Kato, 1925 is transferred to Auritibicen as Auritibicen sp. aff. japonicus comb. n., and Terpnosia sp. aff. vacua Olivier, 1790 is transferred to Yezoterpnosia Matsumura, 1917 as Yezoterpnosia sp. aff. vacua comb. n. The generic placement of two other fossils is changed to reflect current classification, those species now being Auritibicen bihamatus (Motschulsky, 1861) and Yezoterpnosia nigricosta (Motschulsky, 1866).         Two species, Davispia bearcreekensis Cooper, 1941 and Lithocicada perita Cockerell, 1906, are transferred from the subfamily Cicadinae to the Tibicininae, tribe Tibicinini. Cicadatra serresi (Meunier, 1915) is also transferred from the Cicadinae to the Cicadettinae because the Cicadatrini have recently been transferred from the Cicadinae to the Cicadettinae (Marshall et al. 2018).         Miocenoprasia grasseti Boulard and Riou, 1999 is transferred from the tribe Prasiini to the Lamotialnini. Tymocicada gorbunovi Becker-Migdisova, 1954 is transferred from the Dundubiini to the Cryptotympanini; Paracicadetta oligocenica Boulard & Nel, 1990 is transferred from the Cicadettini to the Pagiphorini and Minyscapheus dominicanus Poinar et al., 2011 is assigned to the Taphurini. Names of species once considered to belong in Cicadidae, but now excluded, are listed with explanation.